Payroll System Design With SDLC (System Development Life Cycle) Approac: Payroll System Design With SDLC (System Development Life Cycle) Approac - Mhd. Dominique Mendoza; Tansa Trisna Astono Putri (Institute of Computer Science (IOCS), 2020)
The HR technologies are predominantly used for HR administrative applications, including payroll and benefits administration, this research has profound implications on the evaluation of their effectiveness. A failure to pay people on time and the right amount can cause immense employee dissatisfaction and distress which in turn can severely dent the employer branding.By adopting the system development life cycle (SDLC), this study captures the key factors that should have been taken into account in designing, implementing and rolling out the new payroll system at PT. Faramiga Sindo Energi. The factors that contribute to the success or failure of project implementation are the same which reinforce their reliability and validity.By using the payroll system, the resulting payroll information is more complete, efficient, fast and precise than the previous system which always experiences delays in presenting payroll report information. With the implementation of the program that has been designed, the system can provide convenience in the process of calculating salaries and can find out the salary report quickly and can be requested at any time when needed.